Clinical Assessment of Dysexecutive Syndromes. - Campbell III, John J.; Tisher, Annya (Psychiatric Times, 2014)
The article offers information on the continuing education/continuing medical education (CE/CME) activity involving the clinical assessment of dysexecutive syndromes that is offered on April 20, 2014 to April 20, 2015. One of its objectives is to review the functional neuroanatomy of the frontal-subcortical system. The activity is chiefly aimed for such health care professionals as psychiatrists, psychologists, and primary care physicians.